2014
DOI: 10.1016/j.bbadis.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Abeta, oxidative stress in Alzheimer disease: Evidence based on proteomics studies

Abstract: The initiation and progression of Alzheimer disease (AD) is a complex process not yet fully understood. While many hypotheses have been provided as to the cause of the disease, the exact mechanisms remain elusive and difficult to verify. Proteomic applications in disease models of AD have provided valuable insights into the molecular basis of this disorder, demonstrating that on a protein level, disease progression impacts numerous cellular processes such as energy production, cellular structure, signal transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 140 publications
(148 reference statements)
5
121
0
3
Order By: Relevance
“…Oxidative damage has been reported in AD mice 17,22,34,35 and lipid peroxidation products, such as 4-HNE, 36 have been found to play an important role in AD-related neurodegeneration. Since 4-HNE has been recognized as an endogenous PPAR β/δ-ligand, 14 the levels of its protein adducts were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative damage has been reported in AD mice 17,22,34,35 and lipid peroxidation products, such as 4-HNE, 36 have been found to play an important role in AD-related neurodegeneration. Since 4-HNE has been recognized as an endogenous PPAR β/δ-ligand, 14 the levels of its protein adducts were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies have correlated features of bone metabolism in women with MDD indicating that depressed women had lower bone mass and lower levels of Ocn compared to healthy subjects [120,121]. Moreover, it is known that the antidepressant drugs SSRIs decrease bone mass and increase the risk of fractures, which is consistent with the role of brain-derived serotonin on bone physiology [118,[122][123][124][125]. Interestingly, it was shown that skeletal health in patients with past, but not current history of MDD was comparable to the one of healthy participants, suggesting that bone mass has been normalized after SSRI treatment.…”
Section: Neuropsychological Disorders Associated With Bone Physiologimentioning
confidence: 95%
“…Therefore, we speculate that oligomerization propensity depends on the ability to form long-lived dimers, and the high ratio between type 2 and type 1 A30P dimers promotes the oligomerization pathway. Additional dimer stabilization can be provided by oxidation (58,59) and/or nitration (60) processes that could promote protein aggregation in vivo.…”
Section: Role Of Mutations In A-syn Dimerization and Aggregationmentioning
confidence: 99%